Symmetry properties of one- and two- electron molecular integrals - Brailsford, David F.; Hall, George G. (John Wiley & Sons Inc., 1971)
The maximum numbers of distinct one- and two-electron integrals that arise in calculating the electronic energy of a molecule are discussed. It is shown that these may be calculated easily using the character table of the symmetry group of the set of basis functions used to express the wave function. Complications arising from complex group representations and from a conflict of symmetry between the basis set and the nuclear configuration are considered and illustrated by examples.